Analisis Penguatan Kelembagaan Ekonomi Petani pada Komunitas Petani Padi di Lokasi Food Estate - Yoyon Haryanto; Momon Rusmono; Aminudin Aminudin; Titis Pury Purboingtyas; Gunawan Gunawan (Jurnal Penyuluhan, 2022)
The Farmer's Economic Institution (FEI) was formed due to similarities, having the aim of managing their farming business on the basis of togetherness and fulfillment of facilities. The presence of the food estate program provides acceleration in its growth, but does it have a good impact on the performance of the institution. The purpose of this study was to described the institutional performance that supports FEI in food estate locations, analyze the dominant factors that affect FEI in food estate locations and formulate a strategy for operationally developing FEI at food estate locations. This study used a survey method with purposive sampling technique, obtained 40 farmers who are members of farmer institutions supporting the formation of FEI in the food estate of Pulang Pisau, Central Kalimantan. Data collection was carried out from February to May 2022. Data processing used descriptive techniques and Partial Least Square. The results show that the variables that have a strong influence on the institutional character are social aspects and profitability aspects, with the characteristics of its members being having a relatively low level of education and having fairly good business experience with good technical aspects but weak in managerial mastery.